Biologging reveals rapid movements of harbour seals between freshwater and marine habitats in the subarctic - Katie R.N. Florko; David J. Yurkowski; C-Jae C. Breiter; Steven H. Ferguson; Holly E.L. Gamblin; Adam Grottoli; Andrea Nace; Courtney R. Shuert; Stephen D. Petersen (Frontiers in Marine Science, 2024)
Biologging tools can provide invaluable information on the movement and behaviour of animals, facilitating the elucidation of ecological dynamics, especially for wide-ranging species, and supporting conservation and management efforts. Harbour seals ( Phoca vitulina ) exhibit extensive habitat plasticity in their vast range across the northern hemisphere, with likely recent increases in abundance at northern latitudes, yet details of their movement behaviour in subarctic areas remain largely unknown. We used satellite-telemetry data, including nearly 5,000 locations and over 12,000 dives, obtained from six harbour seals tagged in western Hudson Bay from 2021 to 2023, to address the knowledge gap on their movement behaviour between marine and freshwater habitats in subarctic regions. We document the behavioural patterns, transit speeds, and diverse aquatic system usage, including detailed records of a harbour seal track traversing over 170 km upriver on three separate trips along the Seal River, Canada. Notably, we observed a rapid downstream transit from the Seal River to Hudson Bay, covering 214 km within a single day. Additionally, we highlight the prevalence of short dive durations in the Seal and Churchill Rivers, in contrast to longer dive durations in Hudson Bay. These insights complement existing evidence of harbour seal occurrences and river use at northern latitudes, as well as enhance our understanding of harbour seal movement ecology within Hudson Bay which can be used to better inform conservation and management strategies between connected freshwater and marine environments in the Arctic.